Acetylcholinesterase Inhibitors and Drugs Acting on Muscarinic Receptors- Potential Crosstalk of Cholinergic Mechanisms During Pharmacological Treatment - Soukup, Ondrej; Winder, Michael; Kumar Killi, Uday; Wsol, Vladimir; Jun, Daniel; Kuca, Kamil; Tobin, Gunnar (Current Neuropharmacology, 2017)
Background: Pharmaceuticals with targets in the cholinergic transmission have been used for decades and are still fundamental treatments in many diseases and conditions today. Both the transmission and the effects of the somatomotoric and the parasympathetic nervous systems may be targeted by such treatments. Irrespective of the knowledge that the effects of neuronal signalling in the nervous systems may include a number of different receptor subtypes of both the nicotinic and the muscarinic receptors, this complexity is generally overlooked when assessing the mechanisms of action of pharmaceuticals. Methods: We have search of bibliographic databases for peer-reviewed research literature focused on the cholinergic system. Also, we have taken advantage of our expertise in this field to deduce the conclusions of this study. Results: Presently, the life cycle of acetylcholine, muscarinic receptors and their effects are reviewed in the major organ systems of the body. Neuronal and non-neuronal sources of acetylcholine are elucidated. Examples of pharmaceuticals, in particular cholinesterase inhibitors, affecting these systems are discussed. The review focuses on salivary glands, the respiratory tract and the lower urinary tract, since the complexity of the interplay of different muscarinic receptor subtypes is of significance for physiological, pharmacological and toxicological effects in these organs. Conclusion: Most pharmaceuticals targeting muscarinic receptors are employed at such large doses that no selectivity can be expected. However, some differences in the adverse effect profile of muscarinic antagonists may still be explained by the variation of expression of muscarinic receptor subtypes in different organs. However, a complex pattern of interactions between muscarinic receptor subtypes occurs and needs to be considered when searching for selective pharmaceuticals. In the development of new entities for the treatment of for instance pesticide intoxication, the muscarinic receptor selectivity needs to be considered. Reactivators generally have a muscarinic M2 receptor acting profile. Such a blockade may engrave the situation since it may enlarge the effect of the muscarinic M3 receptor effect. This may explain why respiratory arrest is the major cause for deaths by esterase blocking.
Keywords: acetylcholinesterase